Interprofessional education in the rural environment to enhance multidisciplinary care in future practice: Breaking down silos in tertiary health education. (13th May 2021) - Reed, Krista; Reed, Buck; Bailey, Jannine; Beattie, Karen; Lynch, Elizabeth; Thompson, Jane; Vines, Robyn; Wong, Kam Cheong; McCrossin, Tim; Wilson, Ross
Abstract: Objective: Western Sydney University has implemented a rural interprofessional learning programme to promote collaborative care approaches to enhance cross‐discipline communications, improve knowledge and clarity of roles and improve patient care and outcomes. Design: Rural interprofessinal learning is an interprofessional educational approach, consisting of simulations of complex health events. Simulation methodology frames the study with a focus on human interaction. A mixed‐methods evaluation has been conducted, incorporating pre‐ and post‐ event participant surveys along with semi‐structured focus groups. Setting: Simulations are conducted in the rural setting, including community settings, working farms and rural hospitals. Main Outcome Measures: Reflexive thematic analysis was used to identify themes measuring students' perceptions of interdisciplinary care, knowlede of other health discipline roles and skills and how they believe the exercise will influence their future practice. Facilitator feedback regarding the efficacy of the simulations was also recorded and analysed using reflexive thematic analysis. Participants: Care of simulated patient(s)/bystander(s) is primarily provided by paramedicine, nursing and medical students; however, increasing interest has expanded the programme to include students from a range of allied health professions. Simulations are facilitated by a multidisciplinary team of experienced practitioners and specialists. Intervention: Four rural interprofessional learning events have been held. Results: 120 students have participated in the evaluation. Findings include increased understanding of the contributions of other disciplines in enhancing patient care, team approaches, cross‐discipline communication and a need to engage in collaborative care in future practice. Conclusion: Creating a collaborative learning environment creates a culture of multidisciplinary care, enhancing patient care and improving outcomes. The rural interprofessional learning model is an effective interprofessional educational approach, which can be repeated, refined and improved for continual professional development.